2021
DOI: 10.1002/jmv.26914
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of corticosteroid in patients with COVID‐19: A multi‐center retrospective study and meta‐analysis

Abstract: Purpose To evaluate the efficacy of corticosteroids on COVID‐19 patients with different levels of disease severity. Methods In our multicenter study, 543 patients with confirmed COVID‐19 were classified as Non‐severe group and Severe group, and then were compared respectively for all‐cause mortality and length of hospital stay between those who received corticosteroids and not. By searching in PubMed, Web of Science, Embase and CNKI, we identified 13 retrospective studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
(90 reference statements)
0
17
1
Order By: Relevance
“…The duration of fever was similar between the two groups. Previous studies showed that corticosteroid therapy could shorten the duration of fever in patients with severe COVID-19 compared to standard therapy [10,22]. However, the present results suggest that the duration of fever and the type and dose of corticosteroid therapy might not be related.…”
Section: F I G U R E 1 Correlation Between the Duration Of Oxygen The...contrasting
confidence: 85%
See 1 more Smart Citation
“…The duration of fever was similar between the two groups. Previous studies showed that corticosteroid therapy could shorten the duration of fever in patients with severe COVID-19 compared to standard therapy [10,22]. However, the present results suggest that the duration of fever and the type and dose of corticosteroid therapy might not be related.…”
Section: F I G U R E 1 Correlation Between the Duration Of Oxygen The...contrasting
confidence: 85%
“…The third factor was the severity of COVID-19. Several reports have supported corticosteroid use to treat patients with severe or critical COVID-19 and avoidance of corticosteroids for those with non-severe COVID-19 [9,11,21,22]. Although the optimal type of corticosteroids that would provide good clinical outcomes for patients with severe or critical COVID-19 are still unknown, methylprednisolone reportedly achieved higher lung tissue-to-plasma levels compared to dexamethasone in animal models [23].…”
Section: F I G U R E 1 Correlation Between the Duration Of Oxygen The...mentioning
confidence: 99%
“…Steroids were administered to more cases than controls. These drugs have been associated with potential delayed VC, 33 although this evidence has been questioned by different studies. 30 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Of these 490 patients, 54.7% achieved VC during hospitalization, while the remaining 45.3% reached VC during the post-discharge follow-up period. Median time to VC was 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) days.…”
Section: Sars-cov-2 Clearancementioning
confidence: 99%